Rare bird sighting for Peregrine Falcon at Bettendorf in 1996 - Saul, Ethel E.et al (1996)
Rare bird sighting for a Peregrine Falcon at Bettendorf in Scott County, IA on December 22, 1996. Epson - sheet feed